Support for State Centralism in Reformatory China (Czech Journal of International Relations, 2002)
Wang Shaoguang - Hu Angang: The Chinese Economy in Crisis: State Capacity and Tax Reform. 1st ed. An East Gate Book, Studies on Contemporary China, Armonk: Sharpe, 2001, 285 s., ISBN 0765607662.